Diphoton signals for large extra dimensions at the Fermilab Tevatron and CERN LHC - Éboli, O. J P [UNESP]; Han, T.; Magro, M. B.; Mercadante, P. G. (American Physical Society (APS), 2000)
We analyze the potentiality of hadron colliders to search for large extra dimensions via the production of photon pairs. The virtual exchange of Kaluza-Klein gravitons can significantly enhance this process provided the quantum gravity scale (MS) is in the TeV range. We studied in detail the subprocesses qq̄→γγ and gg → γγ taking into account the complete standard model and graviton contributions as well as the unitarity constraints. We show that the Fermilab Tevatron run II will be able to probe MS up to 1.5-1.9 TeV at 2σ level, while the CERN LHC can extend this search to 5.3-6.7 TeV, depending on the number of extra dimensions. ©2000 The American Physical Society.